The Participation of Women in Wars and their SelfWritings: An Analytical Review (2024)
This feminist-oriented text revolves around methodologicaldiscussions regarding women's participation in different wars, specifically their writing processes within the context of armed conflicts. These reflections shed light on how certain nations shape gendered mechanisms of exclusion and inclusion, which, when undergoing social crises, produce experiences, junctures, ruptures, and continuities at the borders that individuals and societies can (or cannot) cross. Subsequently, the text analyzes how certain studies on wars position women as subjects who strategically act and construct their identities, environments, and narratives through the written word, both at a personal, societal, political, and activist level. By problematizing the relationship between war, nation, gender, and writing, it isrevealed how gender, both masculine and feminine, is moulded, (re)produced, and (re)defined, and how it naturalizes, justifies, and legitimizes the existence of wars and nations.